Smoke Automation and Regression Testing on a peer-to-peer lending Website with the Data-DrivenTesting Method - Margaret Teacher Banjarnahor; Lucia Sri Istiyowati (Ikatan Ahli Informatika Indonesia (IAII), 2022)
Software testing is considered as one of the most important processes in software development as it checks whether the system meets the requirements and specifications of the users. The testing process manually or automatically aims to ensure that the main features are not errors and function during development. The manual process frequently causes the publication time of a feature could not to be punctual. This study aims to create an automation script with the data-driven testing method during smoke and regression testing to ensure the quality, especially the main functions or features, can run normally and not be disturbed by the development of new features that are easily understood. One of Various decent automation tools for testing web applications is Katalon Studio which is based on the Selenium tool. The results of the research that have been carried out show that the process of automation of software testing by applying a script automation tool made with Katalon Studio which applies the data-driven testing method is very good with an achievement rate of 80,21%. The automation tools that are built are easy to use, can be learned quickly, are not too complicated and make users want to use it again.